A systematic review and meta-synthesis of the impact of becoming parents on the couple relationship. (June 2018) - Delicate, Amy; Ayers, Susan; McMullen, Sarah
Abstract: Background: the transition to parenthood (TTP) is associated with changes to a couple's relationship. Quantitative evidence shows the TTP is associated with reduced satisfaction and quality of a couples' relationships. Qualitative research provides information on the lived experience of couples in the TTP so can provide a more in-depth understanding of the impact. This review therefore aimed to synthesise qualitative research of the perceived impact of the TTP on a couple's relationship in contemporary Western society. Design: a systematic search was conducted of nine databases and grey literature. Key author, citation and reference searches were also undertaken. Papers were included if they presented qualitative data of romantic partner relationships during the TTP with parents aged 18 or over. Studies were restricted to those conducted from 1996 in Western societies. Analysis was conducted using meta-ethnography. Findings: searches identified 5256 papers. After applying inclusion criteria 12 papers were included in the meta-synthesis. Six main themes were identified: (1) Adjustment Phase (a period of change in the relationship), (2) Focus on the Baby (with a sub-theme of feeling unprepared for the relationship impact), (3) Communication (shifts in communication patterns and importance), (4) Intimacy (changes to sexual relations, romance and closeness), (5) Strain on the Relationship (short-term or prolonged), and (6) Strengthened Relationships (deepening of connection and new affinity). Except for the themes of Strain on the Relationship and Strengthened Relationships, the findings showed the TTP had positive and negative impacts on couples' relationships. Key conclusions and implications for practice: the review highlights a range of TTP relationship issues that couples experience and may require help with. Health care professionals working with parents in the TTP may be able to provide support through antenatal education that includes preparation for relationship changes, and provision of postnatal support to identify and overcome problems. Highlights: The transition to parenthood can impact upon a couple's relationship. Some parents report feeling unprepared for the impact on their relationship. Six themes of relationship impact are presented including Strain and Strength. Relationship strain can be short-term and strength can transpire in the long-term. The presented themes contain examples of positive and negative effects.